Deciphering consciousness: The role of corticothalamocortical interactions in general anesthesia - Yuxi Zhou; Shiqian Huang; Tianhao Zhang; Daling Deng; Li Huang; Xiangdong Chen (Pharmacological Research)
General anesthesia is administered to millions of individuals each year, however, the precise mechanism by which it induces unconsciousness remains unclear. While some theories suggest that anesthesia shares similarities with natural sleep, targeting sleep-promoting areas and inhibiting arousal nuclei, recent research indicates a more complex process. Emerging evidence highlights the critical role of corticothalamocortical circuits, which are involved in higher cognitive functions, in controlling arousal states and modulating transitions between different conscious states during anesthesia. The administration of general anesthetics disrupts connectivity within these circuits, resulting in a reversible state of unconsciousness. This review elucidates how anesthetics impair corticothalamocortical interactions, thereby affecting the flow of information across various cortical layers and disrupting higher-order cognitive functions while preserving basic sensory processing. Additionally, the role of the prefrontal cortex in regulating arousal through both top-down and bottom-up pathways was examined. These findings highlight the intricate interplay between the cortical and subcortical networks in maintaining and restoring consciousness under anesthesia, offering potential therapeutic targets for enhancing anesthesia management.